Small-signal modeling and wide-band oscillation analysis with the high proportion of renewable energy integrated through LCC-HVDC - Jiang, Kezheng; Liu, Dan; Cao, Kan; Hu, Pan; Xiong, Ping; Wu, Yingzi (Frontiers in Energy Research, 2023)
With the high proportion of renewable energy through HVDC transmission into the grid and the application of high proportion of power electronic equipment, in the modern power system, the traditional electromagnetic conversion equipment represented by synchronous generator is gradually replaced by power electronic equipment, which in a high level has been affecting the dynamic behavior of the power system. In recent years, the wide-band oscillation problem of unknown mechanism continues to appear in power systems, which poses a major threat to the security, stability and operation of power systems. Therefore, based on the typical oscillation event, this paper constructs a typical small-signal model of the new power system which composed of synchronous generator, HVDC transmission and renewable energy generation equipment, the model is suitable for the analysis of wide-band oscillation problem of new power system with renewable energy as the main body. Comparison of time-domain response with detailed time-domain model shows that the proposed can well reflect the dynamic behavior of the detailed time-domain model. Based on the model, the influence of access position, access proportion and control mode of renewable energy integrated through LCC-HVDC on the wide-band oscillation characteristics of the system is analyzed, and the correctness of the analysis is verified by the detailed time-domain model.